A Dialética Do Abstrato E Do Concreto No Livro I De O Capital: A Processualidade E A Interrelação Entre Trabalho E Do Trabalho Abstrato. - Canel, Jose Janio Camelo [UNIFESP] (2018)
We Should Treat A Fundamental Subject On Abstract Work And Work, Not Marx's Theoretical Framework, In A Dialectical Perspective - Identity And Difference Of Concepts. For Example, These Cathegories, A Closed And Concise Definition, Once Appeared As Something Confusing And Obfuscated - To Some Authors And Currents. However, In Capital, Both Work (Arbeit) And Abstract Human Work (Abstract Menschliche Arbeit) - Can Be Thought Of As Different Or Opposing, But An Analysis Must Be Done That Allows To Reveal Its Origins, Nature And Functions. In This Sense, It Sends The Problem Of The Above Categories Into The Concrete Historical Processes, And On The Other Hand, Submit As If It Were An Abstraction That Can Serve As A Tool For Elucidation And Possible, Point To A Solution Of The Problem: The Dialectical Relationship Between Work And Abstract Work.